Chemical contrast in soft x-ray ptychography - Zeitz, Mike; Senkbeil, Tobias; Gorniak, Thomas; Reese, Michael; Giewekemeyer, Klaus; Gleber, Sophie-Charlotte; Salditt, Tim; Rosenhahn, Axel (Physical review letters, 2011)
The unique strengths of x-ray microscopy are high penetration depth and near-edge resonances that provide chemical information. We use ptychography, a coherent diffractive imaging technique that disposes of the requirement for isolated specimens, and demonstrate resonant imaging by exploiting resonances near the oxygen K edge to differentiate between two oxygen-containing materials. To highlight a biological system where resonant ptychography might be used for chemical mapping of unsliced cells, reconstructions of freeze-dried Deinococcus radiodurans cells at an energy of 517 eV are shown.